Inkubasi Usaha Kemitraan untuk Mendukung Wisata Alam Berkelanjutan di Desa Tlogo, Wonosobo - Adi Nugroho; Aziz Setyawijaya NP; Shavira Nofi Safitri; Suryaning Prastuti; M. Taufik Ridho; Ayu Dini Kartika Putri (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2021)
Sustainable tourism maintains the balance between environment, social and economy. Sustainable tourism development requires participation from broader group of people. The program aims to develop community economic business partnerships as a suporting system for an ecotourism site, as what has been implemented in Wisata Alam Seroja which is located in Tlogo, Wonosobo. The village is situated in the hills of Dieng and has views of the Telogo Menjer and the nature of Bukit Seroja. The destination has been opened since 2015 and has only benefited the Tourism Awareness Community Group (Kelompok Sadar Wisata or POKDARWIS). The development of sustainable nature tourism is expected to provide and to make an impact for wider community. Incubation method was employed to empower the Community Economic Business Group (Kelompok Usaha Ekonomi Masyarakat Desa or KUEMD). The KUEMD consists of POKDARWIS, farmer group, culinary group, art group and craft group. The program was held from January 2019 to February 2020 and as a result the partnership of the KUEMD of Tlogo is able to become a support system for Wisata Alam Seroja. The program has also successfully connected Wisata Alam Seroja with two tourism marketplaces; Traval.co and Selenago.com.